A legislação da Educação Municipal de São Paulo que rege os Centros de Educação Infantil na etapa entre 3 e 4 anos de idade e sua relação com a realidade - Batista, Izolda Maria (2017)
The main focus of this study is the practice of teachers who work in Early Childhood Education Centers (CEIs) serving groups of children from zero to three years within the São Paulo Municipal School System. This research questions the general policies of the system between 2012 and 2016. It has, therefore, the purpose of understanding how care practices have been implemented in early childhood education with this age group, guided by the following general question: how do CEIs use legislation and organize educational work with children from three to four years of age? The research was based on document analysis and observation of the teaching practices in classes of children from three to four years of age, seeking to ascertain, through actions in two units, how the enrollment legislation, organization of the unit, creation of class groups, and educational activities are implemented. The documents analyzed were considered external and internal, with the latter being composed of the political-pedagogical project, internal regulations, the school and teachers’ pedagogical projects. The study of these documents aims to provide information on their effectiveness, through both the teachers’ work and the school's actions, and to comprehend their changes in the daily work of the schools as observed during the middle months of the 2016 school year. Vygotsky and Falk’s theories give a historical-cultural perspective about the education of young children. The research also draws on Licínio Lima’s concept of normative infidelity as a sociological approach to analyzing the possible alterations from the legislation practiced by the schools. Rockwell (2009) also provided theoretical support. The methodological pathway is based on some principles of ethnographic research, making it possible to seek information in documents and from the observation of situations and experiencing certain facts. The results indicate several alterations in the schools’ actions when compared to the official definitions, many of them interfering in a negative way in the educational processes, confirming the hypothesis that there are changes to the general norms and the construction of individual norms in each unit